PERKEMBANGAN PARADIGMA DEMOKRASI PANCASILA DALAM PEMBANGUNAN HUKUM DI INDONESIA - Topan Indra Karsa (Keadilan : Jurnal Fakultas Hukum Universitas Tulang Bawang, 2019)
The purpose of this research is to explore the history and process of development and application of Pancasila democracy in Indonesia. The concept of Pancasila democracy in legal development in Indonesia is based on kinship and mutual cooperation aimed at the welfare of the people, which contains elements of religious awareness, based on truth, love and noble character, has an Indonesian personality and is sustainable. The research method used is normative legal research using library materials. The development of democracy experiences fluctuations that affect the joints of social life. The implementation of Pancasila democracy in Indonesia is characterized by religious nationalism, not secular nationalism. The concept of Pancasila democracy does not originate from the notion of individualism that has developed in the west, although it cannot be denied that liberal values ​​that shape democracy in the west, such as equal rights for citizens, freedom of opinion as the main pillar of democracy have a strong influence on the enrichment of Pancasila democracy. Keywords : Democracy, Pancasila, Legal Development